Pengaruh Non Performing Loan dan Loan to Deposit Ratio Terhadap Return On Asset - Nilta Alfi Rizqi (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
This study aims to determine whether there is an effect of Non Performing Loans and Loan To Deposit Ratio on Return On Assets partially or simultaneously. The method used in this research is descriptive verification method with a quantitative approach which is sourced from the annual financial statements of state-owned banks and private banks and literature studies. The sampling technique was using purposive sampling technique. The data used are secondary data analyzed through descriptive analysis and verification of the validity of multiple linear regression test data and hypotheses using the T test and F test coefficient of determination. This study uses the SPSS version 22 software program to process data. The results of this study indicate that partially non-performing loans have a significant negative effect on Return on Assets and the Loan to Deposit ratio has no effect on Return on Assets. Meanwhile, simultaneously the Non Performing Loan and the Loan To Deposit Ratio simultaneously have a significant effect on Return On Assets.